An overview of ecological status, vulnerability and future perspectives of European large shallow, semi-enclosed coastal systems, lagoons and transitional waters - Newton, Alice (2019)
The paper gives an overview of some of the large, shallow, semi-enclosed coastal systems (SECS) in Europe, These SECS are important both from the ecological and the economic perspective (socioecological systems) and provide many valuable ecosystem goods and services. Although some of the systems are transitional waters under theWater Framework Directive, this is not the case for all of the systems. The paper adopts a Driver-Pressure-State-Impact-Response approach to analyse the ecological status, vulnerability and future perspectives of these systems in the context of global change.